Simulation of Grain Structure Formation of Ti-46at. %Al Alloy During Directional Solidification with CAFE Model - LIU Dong-rong; LU Hai-yang; GUO Er-jun (Journal of Harbin University of Science and Technology)
In order to deeply understand the mechanisms responsible for the grain structure evolution during directional solidification of Ti-46at. % alloy，characteristics of grain structure were simulated using CAFE model ( Cellular Automaton-Finite Element) . CAFE model was validated by comparisons with microgravity experiments from a reference. Influences of nucleation undercooling and natural convection intensity on columnar-to-equiaxed transition ( CET) ，grain size，grain elongation and segregation were numerically investigated. Simulated results show that a fully equiaxed grain structure is obtained by lowering the nucleation undercooling. Increasing flow intensity aggravates intergranular segregation，but barely has effects on variations of grain structure morphology and distributions of grain size and elongation. With a high nucleation undercooling，CET occurs. By strengthening fluid flow，the occurrence of CET is retarded，a mixed structure of elongated and equiaxed grains is formed，both grain sizes and elongations are increased and segregation is enhanced. CAFE model can be used to predict grain structure evolution during solidification of Ti-46at. %Al and to analyze the controlling mechanisms.